Use of Phenobarbital to Treat Neonatal Abstinence Syndrome From Exposure to Single vs. Multiple Substances - Kushnir, Alla; Garretson, Cynthia; Mariappan, Maheswari; Stahl, Gary (Frontiers in Pediatrics, 2022)
Drug use in pregnancy is a major public health issue. Intrauterine exposure to opiates may lead to Neonatal Abstinence Syndrome (NAS). Little consensus exists on optimal therapy, especially for those exposed to multiple drugs. We aim to determine whether the use of opiates alone versus in combination with phenobarbital will affect short-term neonatal outcomes. This retrospective review of infants admitted to the Neonatal Intensive Care Unit (NICU) included newborns ≥35 weeks gestation exposed to opiateopioids, or multiple substances including opiateopioids, in utero. Treatment with opiates alone, and addition of phenobarbital as initial therapy versus rescue, was evaluated. Out of 182 newborns, 54 (30%) were exposed to methadone alone versus 128 (70%) to multiple drugs. Length of stay (LOS) in the hospital was not significantly affected (p=0.684) by single versus multiple drug exposure in-utero. Treatment of NAS with opiate alone resulted in shorter LOS (27 days), as compared to those treated with opiate and phenobarbital (45 days, p<0.001). LOS was further prolonged in those treated with phenobarbital as a "rescue" medication in addition to an opiate (49 days, p<0.0001). There was a significant increase in LOS and duration of opiate treatment for all infants treated with phenobarbital, both in those exposed to opiates alone, and to multiple substances in-utero.